Comprehending the potential of metallic, lipid, and polymer-based nanocarriers for treatment and management of depression. (February 2022) - Patel, Rashmin B.; Rao, Hiteshree R.; Thakkar, Dinesh V.; Patel, Mrunali R.
Abstract: The World Health Organization (WHO) ranked depression as the third leading cause of global burden of disease in 2004, and it is predicted to overtake it and move to first place by 2030. It is a mental disorder that causes significant changes in the mood and day-to-day activity of an individual. Various approaches already exist for treating depression but, none of them are completely successful in treating depression. At present, discovering a new medication or delivery mechanism that can manage depression safely and efficiently is a huge challenge. Conventional formulations used in the management of depression have drawbacks like limited penetration, frequent dosing, toxicity, patient compliance concerns as well as brain barriers which are a big hurdle for antidepressant drugs to reach the brain through conventional formulations. Nano-based formulations are gaining popularity as one of the possibilities to overcome the limitations of conventional formulations by reducing the dose and dosing frequency, increasing the efficacy as well as proving it to be safe and effective means of treating depression. This review targets the neurochemistry and pathophysiological concerns of depression, strategies and problems of conventional therapies, and also recent advances in the metallic, lipid, and polymer-based nanoformulations for a variety of antidepressants. A detailed discussion of the expediency of various nanoformulations like liposomes, nanostructured lipid carriers, solid lipid nanoparticles, ethosomes, nanocapsules, dendrimer, gold and silver nanoparticles are addressed in the current review. In essence, nanoformulations hold great promises for the treatment of depression as they provide a platform with high penetration potential, targeted transmission, and improved protection and efficacy. Graphical abstract: Image 1 Highlights: Depression is more than ordinary sadness. It is a disorder with many more symptoms than feeling sad. Treatment of depression must restore proper functioning of the BBB and balance neurotransmitters in the brain. Nanoformulations are garnering considerable interest than conventional formulations for effective depression treatment.